2004
DOI: 10.1016/j.agecon.2004.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A household hedonic model of rice traits: economic values from farmers in West Africa

Abstract: New crop varieties often have been promoted in developing countries based upon superior yield vis-a-vis locally available varieties. This research presents a hedonic price model for upland rice by drawing upon the input characteristics and consumer good characteristics model literature. Model specification tests determine that a combination of production and consumption characteristics best explains the willingness to pay for new upland rice varieties. The household model specification determined that five tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 28 publications
3
30
0
4
Order By: Relevance
“…Though surprising, these findings coincide with those obtained by Dalton (2004) in his hedonic analysis of the economic value of rice traits. The model estimated for all respondents suggests that, in general, farmers prefer varieties with higher potential yield.…”
Section: Ordered Probit Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Though surprising, these findings coincide with those obtained by Dalton (2004) in his hedonic analysis of the economic value of rice traits. The model estimated for all respondents suggests that, in general, farmers prefer varieties with higher potential yield.…”
Section: Ordered Probit Resultssupporting
confidence: 85%
“…Finding similar patterns with the application of a hedonic analysis, Dalton (2004) concluded that although yield has served as a defining factor for promoting a new variety for official release, high yield was not a significant determinant of farmer WTP for new rice varieties in West Africa. The probit coefficients indicate that these attributes are important determinants of the seed preferences stated by farmers, although, in many cases, the sign of coefficient seems to contradict that sought by rice researchers.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Since the seminal work of Waugh (1928), a number of studies have employed hedonic pricing to examine the price structure of different agricultural products (e.g., Unnevehr, 1986;Parker and Zilberman, 1993;Dalton, 2004;Edmeades, 2007;Amegbeto et al, 2008). Since the seminal work of Waugh (1928), a number of studies have employed hedonic pricing to examine the price structure of different agricultural products (e.g., Unnevehr, 1986;Parker and Zilberman, 1993;Dalton, 2004;Edmeades, 2007;Amegbeto et al, 2008).…”
Section: Framework and Hypothesesmentioning
confidence: 99%
“…Doss (2006) emphasized the advantage of micro-level crosssectional analysis to understand farmer preferences, growing conditions in specific areas and what varietal characteristics are important to farmers. Recent studies accentuated farmer perceptions of varietal traits and their influences on the adoption behavior (Adesina and Zinnah, 1993;Adesina and Seidi, 1995;Adesina and Baidu-Forson, 1995;Edmeades et al, 2008;Hintze et al, 2003;Joshi and Pandey, 2006;Wale and Yalew, 2007;Ramasamy et al, 1999), with particular interest in hedonic pricing (Dalton, 2004;Pingali et al, 2001) and revealed preferences of trait valuation (Useche et al, 2009). In this study, farmer preferences for droughttolerant glutinous rice are of particular interest; thus, traits subjectively selected from PVS breeding program are hypothesized to influence the adoption of RD12.…”
Section: Analytical Frameworkmentioning
confidence: 99%